“No level up!”: no effects of video game specialization and expertise on cognitive performance - Gobet, Fernand; Johnston, Stephen J.; Ferrufino, Gabriella; Johnston, Matthew; Jones, Michael B.; Molyneux, Antonia; Terzis, Argyrios; Weeden, Luke (Frontiers in Psychology, 2014)
Previous research into the effects of action video gaming on cognition has suggested that long term exposure to this type of game might lead to an enhancement of cognitive skills that transfer to non-gaming cognitive tasks. However, these results have been controversial. The aim of the current study was to test the presence of positive cognitive transfer from action video games to two cognitive tasks. More specifically, this study investigated the effects that participants’ expertise and genre specialisation have on cognitive improvements in one task unrelated to video gaming (a flanker task) and one related task (change detection task with both control and genre-specific images). This study was unique in three ways. Firstly, it analysed a continuum of expertise levels, which has yet to be investigated in research into the cognitive benefits of video gaming. Secondly, it explored genre-specific skill developments on these tasks by comparing Action and Strategy video game players. Thirdly, it used a very tight experiment design, including the experimenter being blind to expertise level and genre specialisation of the participant. Ninety-two university students aged between 18 and 30 (M = 21.25) were recruited through opportunistic sampling and were grouped by video game specialization and expertise level. While the results of the flanker task were consistent with previous research (i.e. effect of congruence), there was no effect of expertise, and the action gamers failed to outperform the strategy gamers. Additionally, contrary to expectation, there was no interaction between genre specialisation and image type in the change detection task, again demonstrating no expertise effect. The lack of effects for game specialization and expertise goes against previous research on the positive effects of action video gaming on other cognitive tasks.